PENGARUH MODEL PEMBELAJARAN PROJECT- BASED LEARNING (PJBL) TERHADAP KEMAMPUAN MENULIS TEKS EKSPOSISI PADA SISWA KELAS VIII DI SMP NEGERI 31 MEDAN TAHUN PEMBELAJARAN 2025/2026 - Asnita Hasibuan; Tuti Vina Winata Br Manungkalit; Candra Ronitua (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability of eighth-grade students of SMP Negeri 31 Medan in writing expository texts, especially in developing ideas, constructing fact-based arguments, and systematically structuring the text according to the demands of the Merdeka Curriculum. To overcome this problem, the Project-Based Learning (PjBL) model was implemented which emphasizes active learning through project-based activities. This study aims to determine the effect of PjBL implementation on students' expository text writing abilities. The study used a quantitative approach with a one-group pretest–posttest experimental design. The research subjects were 30 students of grades VIII-6 of SMP Negeri 31 Medan in the 2025/2026 academic year. The instrument used was an expository text writing test given before and after the treatment, with assessments covering text structure, idea development, and accuracy of language use. Data were analyzed using descriptive statistics and t-tests. The results showed an increase in students' writing abilities from an average score of 53.5 in the pretest to 79.0 in the posttest. The percentage of learning completion also increased from 16.67% to 76.67%. The t-test results showed a significance value of p < 0.05, indicating that the implementation of Project-Based Learning (PjBL) significantly influenced the ability to write expository texts. Thus, Project-Based Learning (PjBL) has been proven effective in improving the expository writing skills of junior high school students.